Combined inativation of Escherichia coli by phages and antibiotics - Lopes, Ana Sofia Correia (2018)
Escherichia coli, a non-pathogenic commensal bacterium, can, however, developed more virulent variants that colonize outside the gastrointestinal system. This bacterium is one of the main responsible for moderate and serious infections in the hospital and community environments, being involved in the rapid evolution of fluoroquinolones and third generation cephalosporin resistance. It is estimated that in the coming years the number of deaths caused by resistant bacteria, including even commensal strains, will be very high, leading to an increased need to find alternatives to fight against pathogenic bacteria. An alternative or supplementary approach to antibiotics is phage therapy, which uses lytic bacteriophages (phages) that are able to infect only prokaryotes cells. Several studies have already shown encouraging effects when using phage therapy, however, phage-resistant mutants have been considered a major concern when this method is employed to inactivate pathogenic bacteria. Resistance can be overcome with the combination of phages and antibiotics, which prevents the re-growth of resistant bacteria and reduce more efficiently bacterial density than when used separately. In this study, the effect of combined treatments of phages and antibiotics in the inactivation of E. coli was evaluated. For that, it was used the phage Ec-Bio and the bioluminescent-transformed strain of E. coli. It was tested the antibiotic ciprofloxacin at lethal and sublethal concentrations added at different times (0, 6, 12 and 18 h) in combination with the phage to inactivate E. coli at two multiplicity of infection (MOI), 1 and 100. In general, bacterial inactivation did not increase with the increase of MOI. When the ciprofloxacin was added at different times (6, 12 and 18 h), phage production was similar to the obtained with phage alone, but higher than that observed when ciprofloxacin was added at the same time of the phage. The phage alone caused a reduction of ~2.8 log of E. coli after 12 h of treatment. The mixtures of phage with ciprofloxacin, at sublethal concentrations (1/5 and 1/10 of MIC), did not cause significant differences when compared with the results obtained just with the phage alone, however, after the same time period, at MIC and 2xMIC, the inactivation of E. coli was lower than that obtained with phage alone. Otherwise, the combination of phage and ciprofloxacin at MIC and 2xMIC, reached the maximum rate of inactivation, after 18 and 36 h, respectively, but at these times, re-growth of E. coli was observed when the phage was used alone. A higher difference was observed between the treatment with the mixture phage and antibiotic at MIC and the antibiotic alone than when the antibiotic was used 2xMIC. E. coli was most effectively inactivated when the antibiotic was added after the phage. The efficacy of the combined treatment varied with the antibiotic concentration and the time of antibiotic addition, avoiding bacterial regrowth when the antibiotic was used at MIC and added after 6 h of phage addition. In this case, bacterial resistance was lower than when phages and antibiotics were applied alone (4.0 x 10-7 for the combined treatment, 3.9 x 10-6 for the antibiotics alone and 3.4 x 10-5 for the phages alone). The combined treatment with phages and antibiotics can be effective in reducing the bacterial density, but also to prevent the emergence of resistant variants. However, the antibiotic concentration and the time of antibiotic application are essential factors to be considered in the combined treatment